Implikasi pendidikan formal ke atas pembangunan masyarakat Punan : kajian kes di rumah Arjey, Kuala Mina dan Rumah Ado, Kakus, Tatau - Andy, Ak Salipui. (Universiti Malaysia Sarawak (UNIMAS), 2002)
Education is a necessary ingredient for development in a community. People in a community strongly value the power, influence and the purpose of education. The aim of this study is to assess how formal education functions in term of community development. The obstacle in getting formal education, leader's role in exposing family members to formal education and to identify the nature of job for those who had formal education. From the finding, it was indicated that family leaders play an important role in exposing and supporting their family members to go for formal education. In addition, he supports the family members in terms of the cost of education. He believed that each family member is supposed to have formal education to unsure good job, better salary and most importantly for a better future. Beside that, the study also found that is little difference in the kind of employment between those who get formal education with those wbo no formal education. It can be conclude that Punan community in Sarawak are still left behind in lerms of formal education due to several factors. Nevertheless, they believed that by acquiring formal education the new generation of Punan community would be better off.